Biophysical Description of Multiple Events Contributing Blood Leukocyte Arrest on Endothelium - Robert, Philippe; Touchard, Dominique; Bongrand, Pierre; Pierres, Anne (Frontiers in Immunology, 2013)
Blood leukocytes have a remarkable capacity to bind to and stop on specific blood vessel areas. Many studies have disclosed a key role of integrin structural changes following the interaction of rolling leukocytes with surface-bound chemoattractants. However, the functional significance of structural data and mechanisms of cell arrest are incompletely understood. Recent experiments revealed the unexpected complexity of several key steps of cell-surface interaction : i) ligand-receptor binding requires a minimum amount of time to proceed and this is influenced by forces. ii) Also, molecular interactions at interfaces are not fully accounted for by the interaction properties of soluble molecules. iii) Cell arrest depends on nanoscale topography and mechanical properties of the cell membrane, and these properties are highly dynamic. Here, we summarize these results and we discuss their relevance to recent functional studies of integrin-receptor association in cells from a patient with type III leukocyte adhesion deficiency. It is concluded that an accurate understanding of all physical events listed in this review is needed to unravel the precise role of the multiple molecules and biochemical pathway involved in arrest triggering.